Violations of accuracy in Russian oral public speech of Viciebsk citizens - Novikova, Lidia P. (Journal of the Belarusian State University. Philology, 2019)
The paper views lexical deviations in Russian oral public speech, related to the violation of linguistic accuracy conditions. The research is conducted on the original material, which is a record of fragments of modern Russian oral public speech, presented on TV channels, conferences and meetings. The observance of the basic linguistic conditions of speech accuracy is analyzed: the use of a word that accurately denotes the subject of thought; knowledge of the syntagmatic properties of the word; the exact choice of a word from the synonymic series; the choice of the meaning of a multi-valued word, avoiding ambiguity; clear differentiation of paronyms; knowledge of the meanings of words in a narrow sphere of use. It’s concluded that in Russian oral public speech of educated residents of Viciebsk violations of accuracy are common.
Keywords: oral public speech; accuracy of speech; communicative qualities of speech